GAMBARAN TINGKAT KEJADIAN MISSFILE DAN FAKTOR PENYEBABNYA PADA BAGIAN FILLING REKAM MEDIS DI PUSKESMAS PONTANG - Tri Moedji Hartiningsih; Aprilia Eka Wijayanti (Journal Of Applied Health Research And Development, 2022)
Background: The purpose of this research is to know the description of the Missfile Incidence Rate and its Causes in the Medical Record Filling Section of the Pontang Health Center. The type of research used in this study is descriptive research, which is a research method carried out with the main aim of making an objective description or description of a situation [1] Based on the results of observations and interviews related to the storage system and alignment system at the Pontang Health Center, there is no SOP related to the storage system and alignment system of medical record files. Based on the results of interviews with filling officers of the Pontang Health Center, there is no special officer for the medical record section, especially in the filling section, filling activities at the Pontang Health Center are still carried out by two registration officers. Based on the observations made by the author, the system used at the Pontang Health Center is centralized. Based on the results of observations and interviews, the alignment system of medical record files used at the Pontang Health Center is straight numerical filling (SNF). Based on observations, the means of controlling medical record files in the filling section of the Pontang Health Center uses a shelf made of wood. The results of the recapitulation of the missfile incidence rate above show that the percentage of missfile events is 14.01% with the number of missfile events being 167 medical record files from 1192 medical record files on the storage rack.